SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL EVALUATION OF SOME NEW BENZOTHIAZOLE DERIVATIVES - Chauhan, Deepa; Siddiqui, A. A.; Kataria, Rajkumari; Singh, Robin (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Synthesis, characterization and antimicrobial evaluation of some new 1,3-benzothiazolyl pyrazole derivatives. Methods: Aseries of novel2-[3-(substituted phenyl)-4-formylpyrazol-1-yl]-6-chloro benzothiazole derivatives (5a-g) have been synthesized by cyclization through Vilsmeier-Haack reaction on hydrazones (4a-g)of substituted aromatic ketones with 6-chloro benzothiazol-2-yl hydrazine under microwave irradiation in fairly good yields. All the newly synthesized compounds were characterized by IR, 1HNMR, Mass spectral studies and elemental analysis and were screened for their in vitro antibacterial and antifungal activities also. Results: The results revealed that all 1,3-benzothiazole pyrazole derivatives(5a-g) were synthesized in satisfactory yields and pharmacologically evaluated for their in vitro antimicrobial activity. All the synthesized compounds were in good agreement with elemental and spectral data. Some of the tested compounds showed good to moderate antimicrobial activity against all tested pathogenic bacterial and fungal strains. Conclusion: For the present investigation we have prepared benzothiazole derivatives that are incorporated with pyrazolyl moiety with the hope of potentiating the activity of two such units in the same compound. Compounds 5b, 5c, and 5a showed excellent antibacterial and antifungal activities as compared to reference drugs norfloxacin and ketoconazole. Â